"Marriage was not an option": ethnoreligious mixed marriage in Israel. Issue 1 (2nd January 2022) - Sabbah-Karkabi, Maha
ABSTRACT: This study explores the way Jewish women negotiate their crossing ethnoreligious borders in a deeply divided society through 15 in-depth interviews. Despite social, economic and political exclusion of Palestinians in Israel, in certain circumstances, the ethnic and religious borders are weakening. The core findings have led to three conclusions. First, ethnic mixed marriage occurs between Palestinian men and Jewish women from diverse groups with heterogeneity in their socioeconomic features, which places in doubt previous discourse that this kind of marriage appears among people from marginalized groups in Israel. Second, the ethnic hierarchical relationship between the two groups carries over into their intimate relationships. Third, the rigid borders of ethnoreligious belonging to the Israeli society and the extent of belonging to the Jewish mainstream differ among Jewish immigrants from different origins, produce different types of negotiations among the Jewish women while they are crossing the ethnoreligious borders by marrying Palestinian men.